The Urgency of Personal Data Protection Agencies in Sustaining the Resilience of the Digital World - Dhea Yulia Maharani; Suparno Suparno (Edunity Kajian Ilmu Sosial dan Pendidikan, 2024)
The Industrial Revolution had a significant impact on human life, demonstrated by the quick use of enormous amounts of information. The peculiarity is in this manner directed by Regulation Number 27 of 2022 concerning Individual Information Assurance (UU PDP). The legal framework and foundation for data are provided by the law and/or information exchange activities in Indonesia. Article 58 Paragraph (2) of the UU PDP mandates the establishment of an institution tasked with implementing security for individual data. Because of the powerful idea of information and additional data exchanges, there is an earnestness to lay out a foundation for individual information security. The research will focus on exploring the role and actions of the Government thus far within the framework of individual information insurance before the foundation of the individual information assurance establishment. Moreover, this concentrate likewise assesses the criticalness of laying out an individual information security establishment in keeping up with computerized world versatility. The technique utilized in this examination is regularizing juridical, explained through a rule approach.